The clinical impact of glenoid concavity and version on anterior shoulder stability - Sebastian Oenning, MD; Clara de Castillo; Elena Jacob, MD; Arne Riegel, MD; Philipp A. Michel, MD; Jens Wermers, MSc; Michael J. Raschke, MD; J. Christoph Katthagen, MD (JSES International)
Background: In recent biomechanical studies, the importance of glenoid concavity and version for anterior shoulder stability has been highlighted. With this study, we aimed to assess their clinical relevance as stabilizing factors. We hypothesized that low glenoid concavity and low retroversion are associated with anterior glenohumeral instability. Methods: In this single-center, retrospective case-control study, computed tomography scans of n = 34 patients following acute anteroinferior glenohumeral dislocation between 2015 and 2021 were included. Patients with glenoid fractures and pre-existing glenohumeral pathologies were excluded. In the control group, n = 68 polytrauma patients referred to our level-I-trauma center were included, who showed neither acute nor chronic glenohumeral pathologies. Both groups were matched age- and gender-specifically in a 2:1 ratio. Glenoid concavity was measured according to the bony shoulder stability ratio (BSSR) in anterior-posterior (AP) and superior-inferior (SI) direction. Version was measured by the glenoid vault method. Results: The instability cohort presented with a lower BSSR (SI) compared to the control group (49.8% vs. 56.9%, P = .001). The BSSR (AP) did not differ significantly (30.2% vs. 33.7%, P = .163). A higher retroversion was seen in the instability cohort (−13.1° vs. −11.4°; P = .041). Subgroup analyses showed higher BSSR (SI) in ≥60-year-old patients compared to ≤30-year-old patients. BSSR (AP) and glenoid version did neither differ age- nor gender-specifically. Conclusion: Glenoid concavity is a relevant factor for anterior shoulder stability in the clinical setting. In contrast to recent biomechanical studies, glenoid version appears to have only limited clinical impact on anterior stability. Regarding the individual treatment of anterior glenohumeral instability, glenoid concavity should be focused on as an essential bony stabilizing factor.